2018
DOI: 10.3390/ijms19071853
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between the In Vivo Biodistribution and Therapeutic Efficacy of Adipose-Derived Mesenchymal Stromal Cells Administered Intraperitoneally in Experimental Colitis

Abstract: Mesenchymal stem cells (MSCs) have emerged as a promising treatment for inflammatory diseases. The immunomodulatory effect of MSCs takes place both by direct cell-to-cell contact and by means of soluble factors that leads to an increased accumulation of regulatory immune cells at the sites of inflammation. Similar efficacy of MSCs has been described regardless of the route of administration used, the inflammation conditions and the major histocompatibility complex context. These observations raise the question… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…Alternative routes of administration have been proposed, such as intranodal [ 61 ], intra-articular (IA) [ 62 , 63 , 64 , 65 , 66 ], peri-articular [ 67 ], intra-muscular [ 68 ], and subcutaneous [ 69 ], with good results. This supports the idea that MSC-based therapy is mainly mediated by systemic biological effects [ 70 , 71 , 72 ].…”
Section: Preclinical Studiessupporting
confidence: 85%
“…Alternative routes of administration have been proposed, such as intranodal [ 61 ], intra-articular (IA) [ 62 , 63 , 64 , 65 , 66 ], peri-articular [ 67 ], intra-muscular [ 68 ], and subcutaneous [ 69 ], with good results. This supports the idea that MSC-based therapy is mainly mediated by systemic biological effects [ 70 , 71 , 72 ].…”
Section: Preclinical Studiessupporting
confidence: 85%
“…Some studies show that intraperitoneally injected MSCs disseminate to heart, lung, liver, spleen, and kidney, but do not migrate to the colon (Song et al, 2017b). However, other studies have confirmed that intraperitoneal but not intravenous MSCs could migrate to the inflammatory site of the injured colon (Castelo-Branco et al, 2012;Lee et al, 2018;Lopez-Santalla et al, 2018). Our data showed that CM-Dil-labeled UCMSC SCM and UCMSC S&XFM−CD were only transiently recruited to the injured colon and both UCMSCs exhibited low levels of recruitment and persistence in experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its anti-inflammatory properties, ASC transplantation has appeared to be an effective method for treatment of inflammatory bowel diseases in animal models [103][104][105][106][107][108][109][110]. It was found that ASC administration significantly reduced the secretion of proinflammatory cytokines (tumor necrosis factor-α, interleukin-12, and vascular endothelial growth factor), and improved the clinical disease score and histological parameters in experimentally induced models of murine colitis [103][104][105][108][109][110]. The ASC infusion resulted in a decrease in both clinical inflammatory bowel disease activity index and canine chronic enteropathy clinical activity index, in a group of treated dogs.…”
Section: Animal Modelsmentioning
confidence: 99%